Literacy through literature for elementary school students in semarang city - Cahyaningtyas, Andarini Permata; Purwati, Panca Dewi; Sukasih, Sri; Irvan, Moh. Farizqo (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2024)
Using literary works in language and learning cannot be avoided. For this reason, this research aimed to determine the use of literary works in students' literature learning to support the School Literacy Movement (GLS) at SDN Genuksari 01. There are several research stages in this research: the pre-field, fieldwork, and data analysis stages. The data were collected through interview techniques and questionnaires conducted on 17 classroom teachers and a school principal (18 participants). The data obtained was then processed and analyzed descriptively according to the research flow. Finally, data validity was carried out by triangulating data and sources. This study's result is that most teachers have implemented literary works in literature learning since before the pandemic until now. The sources are from the school library, teachers, or students in the form of printed or digital. This means GLS in SDN Genuksari 01 is supported by using literary works in the literature learning process. However, there are several challenges experienced by the teachers, such as limited sources in the school library, teachers' inability to use IT-based literary works, teachers' limitation in understanding literary material, and students' low interest in reading activities.